2011
DOI: 10.1177/002204261104100405
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and the Duration of Homelessness among Drug-Using Arrestees: Evidence from 30 American Counties

Abstract: We examined risk factors influencing length of homelessness among a sample of drug-using adults booked into jails in 30 American counties during the years 2002-2003. Interviews were conducted with 30,634 arrestees. Multinomial logistic regression (MLR) explored the impact of arrestees' drug use histories, prior experiences with alcohol and drug treatment, prior mental health experiences, and previous criminal justice experiences on membership in one of three housing stability categories. MLR results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Furthermore, homeless adults are more likely to return to jail after incarceration than domiciled adults [ 10 ]. In Texas, more than half of adults released from county jails are rearrested within 1 year [ 11 ], and many of those rearrested are homeless [ 12 ]. In Dallas County alone, 5530 homeless adults were incarcerated in 2013 at an estimated cost of US$12,557,406 (calculated in 2014) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, homeless adults are more likely to return to jail after incarceration than domiciled adults [ 10 ]. In Texas, more than half of adults released from county jails are rearrested within 1 year [ 11 ], and many of those rearrested are homeless [ 12 ]. In Dallas County alone, 5530 homeless adults were incarcerated in 2013 at an estimated cost of US$12,557,406 (calculated in 2014) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incarcerated homeless adults have a variety of risk factors that increase the likelihood of rearrest. For instance, homeless inmates are more likely than domiciled inmates to have histories of mental illness or substance use disorders [ 9 , 12 ]. The research team’s preliminary studies indicated that homeless adults released from jail in the past year were more likely than those not recently incarcerated to have a history of substance use or mental health problems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10] In Texas, more than half of adults released from county jails are re-arrested within one year, [11] and many of those re-arrested are homeless. [12] In Dallas County alone, 5530 homeless adults were incarcerated in 2013 at an estimated cost of $12,557,406. [13] Incarcerated homeless adults have a variety of risk factors that increase the likelihood of rearrest.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, homeless inmates are more likely than domiciled inmates to have histories of mental illness and/or substance use disorders. [9,12] The research team's preliminary studies indicated that homeless adults released from jail in the past year were more likely than those not recently incarcerated to have a history of substance use and/or mental health problems. [14] Thus, there is a strong need for mental health and substance abuse treatment among homeless adults following their release from jail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation